Mycovirus therapy for invasive pulmonary aspergillosis?. (28th February 2019) - van de Sande, Wendy W J; Vonk, Alieke G
Abstract: With the current revived interest in the use of bacteriophages for the treatment of bacterial infections, the study of mycoviruses as novel therapeutic solutions for invasive aspergillosis is the logical next step. Although ssRNA, dsRNA, and ssDNA mycoviruses have been identified, the majority of characterised mycoviruses have dsRNA genomes. Prevalence of dsRNA mycoviruses in Aspergillus spp. varies, and mycoviruses can have different effects on their fungal hosts: hypovirulence, hypervirulence, or a killer phenotype. Therapeutically, extracellular transmission of the mycovirus is essential. DsRNA mycoviruses lack an extracellular phase; however, a single ssDNA mycovirus with homologues in Aspergillus genomes has been described with an extracellular mode of transmission. Mycoviruses can induce hypovirulence or a killer phenotype, and both can be exploited therapeutically. Mycoviruses inducing hypovirulence have been used to control chestnut blight, however for aspergillosis no such mycovirus has been identified yet. Mycovirus encoded killer toxins or anti-idiotypic antibodies and killer peptides derived from these have been demonstrated to control fungal infections including aspergillosis in animals. This indicates that mycoviruses inducing both phenotypes could be exploited therapeutically as long as the right mycovirus has been identified.